ANALYSIS OF THE INFLUENCE OF EXCELLENT SERVICE TRAINING ON INPATIENT SATISFACTION IN RSIA PURI BUNDA MALANG - Widyaningrum, Kurnia; Ahsan, Ahsan (Universitas Brawijaya, Indonesia, 2017)
Increasing the number of patients and hospital performance improvement should be accompanied by improved quality of service. With good quality care, the patient satisfaction will increase and will come back to use the service. Preliminary studies indicate that a decline in the level of patient satisfaction in inpatient units RSIA Puri Bunda. The purpose of this study was to determine differences in patient satisfaction before and after giving excellent service training as well as explore factors that influence service quality of patient satisfaction. This research method is the pre-post quasi-experimental design. Respondents are patients in inpatient units RSIA Puri Bunda who underwent treatment at least 2 days. Total respondents 181 people. The results showed that there was a difference in the satisfaction averages 3.86 P0, P1 and P2 4.29 4.06. Through Mann Whitney test found significant differences in the groups P1 and P2 in the variable product quality with sig 0,010 and emotional factors with sig 0.005. Advice to the management of the hospital is to conduct continuous training in order to reach the expected results.